Mitigating Stunting in Semarang City, Indonesia: A Comprehensive Approach to Better Health and Well-Being - Krisseptiana; Martadi, Nana Storada Dwi (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2024)
Background: Among the 29 districts and 6 cities in Central Java, Semarang City stands out as the urban area with the most substantial reduction in stunting prevalence over a year (2021-2022), from 21,3% to 10.4%, while numerous regions continue to grapple with challenges in lowering rates of stunting. Aims: This study aims to investigate Semarang City's comprehensive strategy for mitigating stunting. Methods: This study used a qualitative case study approach. Utilizing focus group discussions (FGD) and document analysis, representatives from 16 diverse sectors, including health, education, religion, social services, food security, and more, engaged in discussions to synchronize activities and policies to achieve the common goal of stunting reduction. Simultaneously, a comprehensive document analysis was conducted, reviewing relevant documents, reports, and policies across 16 districts in Semarang City. Data analysis employed Miles et al.'s interactive model, involving data condensation, display, and conclusion drawing/verification. Results: The success of stunting reduction in Semarang City is highlighted by relevant regulations, an updated and accurate statistical database, intensive cross-sector coordination, and a synchronized effort across diverse sectors. Furthermore, the city's prudent financial planning is evident through sufficient and on-target budget allocations dedicated to stunting reduction programs. Conclusion: The research the importance of ongoing commitment, adaptability, and collaborative efforts to achieve the ambitious goal of zero stunting by 2024 in Semarang City, suggesting future studies focus on program effectiveness and long-term sustainability.